The Impact of the Urban Lockdown Related to the Corona Pandemic (Covid-19) on Urban Heat Islands in Medina, Saudi Arabia Using Landsat Imagery (Iraqi National Journal of Earth Science (INJES), 2026)
The study discussed the impact of the urban lockdown related to the Covid-19 pandemic on the Urban Heat Island Temperature (UHI) of Medina during the periods 2018-2020-2022. The research relies mainly on processing Landsat 8 using ArcGIS to reveal the relationship between the vegetation cover index (NDVI), the land surface temperature (LST), and the UHI. The study indicates that the NDVI in May 2018 ranged between 0.4350 and -0.0952, which was the lowest value. In May 2020, the value of the NDVI percentage rose between 0.506 and -0.118, while in May 2022, the outcomes showed that the NDVI percentage began to decrease ranging between 0.295 and 0.197. The LST started to decline in the outskirts of urban areas, specifically in Medina. The study found that the NDVI is lower when the LST is higher, while the NDVI is higher when the LST is lower. In 2020, the UHI increased in most urban areas reaching 37°C; in contrast of that increase, the temperature decreased to 11°C. During the entire lockdown period, Madinah witnessed a decrease in UHI in 2020. In 2022, specifically at the end of the lockdown period, Madinah witnessed an increase in UHI reaching 41°C.
Keywords: COVID-19 pandemic, Al Madinah, Land Surface Temperature, Normalized Difference Vegetation Index, Urban Heat Island.